Pembelajaran Berbasis Proyek sebagai Pendekatan Pembentukan Karakter: (Studi pada Mata Pelajaran Akhlak di MA Yapina) - Nurfalah, Samsu; Sidiq Nurdiansyah Sumitra; Muhamad Nasrul Haq; Syaiful Anwar (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the implementation of Project Based Learning (PjBL) in enhancing students’ understanding of moral values in Islamic Religious Education at the tenth grade of MA Yapina. The research is motivated by the urgent need to strengthen character education through learning experiences that are meaningful, contextual, and aligned with the challenges of contemporary moral degradation. Using a descriptive qualitative approach, this study analyzes learning activities, instructional documents, and students’ project outputs to explore how PjBL shapes their comprehension of akhlak as both knowledge and practiced behavior. Findings indicate that PjBL encourages active participation, collaboration, creativity, and reflective thinking, enabling students to interpret moral values through real-life situations and group-based problem solving. Projects assigned to students, such as posters, videos, and thematic presentations, foster deeper understanding because they require the integration of moral concepts into practical tasks. The role of the teacher as a facilitator further supports the learning process by guiding students in inquiry and project management. Despite challenges such as variation in student discipline and time constraints, the overall implementation of PjBL demonstrates positive effects on students’ cognitive and affective grasp of moral values. This study underscores the relevance of PjBL as an innovative pedagogical model for Islamic Religious Education and highlights its potential for strengthening character formation in madrasah settings. It also suggests the need for further research involving direct classroom observations and interviews to enrich empirical evidence on the long-term impact of PjBL on student character development.